Invited Editorial: A Natural-Resource-Based View of the Firm - Hart, Stuart L.; Dowell, Glen (Journal of Management, 2011)
The authors revisit Hart’s natural-resource-based view (NRBV) of the firm and summarize progress that has been made in testing elements of that theory and reevaluate the NRBV in light of a number of important developments that have emerged in recent years in both the resource-based view literature and in research on sustainable enterprise. First, the authors consider how the NRBV can both benefit from recent work in dynamic capabilities and can itself inform such work. Second, they review recent research in the areas of clean technology and business at the base of the pyramid and suggest how the NRBV can help inform research on the resources and capabilities needed to enter and succeed in these domains.